"I Didn't Make It, but...": Deselected Athletes' Experiences of the Talent Development Pathway - Graham Williams; Graham Williams; Áine MacNamara (Frontiers Media S.A., 2020)
The experiences of youth athletes on specialized talent development pathways has received considerable attention in both the media and literature. Despite the low conversion of pathway entrants into senior athletes, the experiences of deselected athletes have received less attention. The purpose of this study therefore was to explore the talent pathway experiences of youth athletes who were deselected from a pathway and to consider how those experiences influenced their life post deselection. Ten participants were purposefully sampled based on their prior involvement in a formalized and selective talent programme. Individual semi-structured interviews were conducted, and data was analyzed via a thematic analysis. Participants identified constructs of the talent development environment, psychobehavioral skills for future development and personal responsibility for future development as facilitators for future success beyond the talent pathway. Specifically, environmental constructs, such as high performance support systems and expectations of professionalism positively contributed toward the acquisition of transferable psychobehavioral skills, such as a determination to be successful, a confidence to back oneself and social maturity. Youth athletes reported feeling empowered to take personal responsibility for development, through attributes such as a commitment to be the best they can be and an intrinsic motivation to succeed. These findings suggest positive experiences, built around the development of transferable skills and behaviors, can accrue from being on the talent pathway. As such, the talent pathway can be a successful foundation for both success in that sport and as a facilitator of success beyond sport.